Capital Allocation by Public and Private Firms - Mortal, Sandra; Reisel, Natalia (Journal of Financial and Quantitative Analysis, 2013)
We compare investment policies across public and private firms in different institutional settings. Using a large cross-country data set, we find that public listed firms are better positioned to take advantage of growth opportunities than private firms. Specifically, public listed firms exhibit higher investment sensitivity to growth opportunities than private firms. This differential, however, only exists in countries with well-developed stock markets. Furthermore, the relative advantage public firms have at allocating capital depends on the degree of agency costs and reliance on external equity.